A Study of Visual Merchandising as a Marketing Tool: Examining the Impact and Effectiveness of Visual Merchandising in Retail Marketing (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Visual Merchandising is expended as an element of uniformity and point of difference in the retail industry. It works on initiating the customers to prepare prompt decision of acquisition. The initiative of this paper is to obtain awareness from the literature of Visual Merchandising and create a substance for future researches in the framework of organized retail. The study covers a meta-analysis of existing researches and tried to find the relationship between Visual Merchandising and customer buying behavior. Visual Merchandising is recognized as an instrument to attract the consumer towards the product and at the same time creating its image which helps in distinguishing distinctly it from competitor’s products. Visual Merchandising is a broadly utilized custom of trade tailor-made as per the requirements of the structured retailers stipulating the involvement of the customer in the shopping experience and prompts purchase instantly Visual Merchandising includes store decorations by tastefully hanging pamphlets, outlook, lighting, etc.